2017
DOI: 10.1007/s11368-017-1820-3
|View full text |Cite
|
Sign up to set email alerts
|

Litter decomposition in peatlands is promoted by mixed plants

Abstract: Purpose. The carbon sink function of peatlands is primarily driven by a higher production than decomposition of the litter Sphagnum mosses. The observed increase of vascular plants in peatlands could alter the decomposition rate and the carbon (C) cycle through a litter mixing effect, which is still poorly studied. Here, we examine the litter mixing effect of a peat moss (Sphagnum fallax) and two vascular plants (Pinus uncinata and Eriophorum vaginatum) in the field and laboratory-based experiment. Materials a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(6 citation statements)
references
References 36 publications
0
5
0
1
Order By: Relevance
“…In this study, no differences were observed to Cacquiring enzymes between treatments (Figure 1B) and these enzymes did not correlate with any differences between the C content in the litter (Table 1). In addition, different types of litter, such as those found in mixed plantations, do not seem to stimulate specifically the activity of β-glucosidase, since other enzymes can play significant roles in this condition (e.g., cellulase) (Leroy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, no differences were observed to Cacquiring enzymes between treatments (Figure 1B) and these enzymes did not correlate with any differences between the C content in the litter (Table 1). In addition, different types of litter, such as those found in mixed plantations, do not seem to stimulate specifically the activity of β-glucosidase, since other enzymes can play significant roles in this condition (e.g., cellulase) (Leroy et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Highly decomposed Sphagnum and Molinia peats were sampled in duplicate (samples A and B) in sites which were intensively studied by D' Angelo et al (2016), Bernard-Jannin et al (2018 and Leroy et al (2018Leroy et al ( , 2019aLeroy et al ( and 2019b. Large undisturbed samples (15´15´25 cm 3 ) were collected between 25 and 40 cm depth when the groundwater table level was close to the soil surface.…”
Section: Field Samplingmentioning
confidence: 99%
“…The residues of peat-forming plants can be divided into two groups based on their resistance to decomposition: (1) the rapidly decomposing fraction, which is not fixed in the botanical composition of the organic layer of peat soils (including leaves of Chamaedaphne calyculata, Menyanthes trifoliata, and other grasses), and (2) the stable fraction, which is permanently fixed in the botanical composition of peat (encompassing all fractions of most shrubs, roots of grasses like Carex (sedges), Scheuchzeria (Scheuchzeria), Eriophorum (cotton grass), and all sphagnum mosses) [9,22,[25][26][27]. Of particular interest is the non-additive effect that arises when the residues of different plant species is mixed [28,29].…”
Section: Introductionmentioning
confidence: 99%